2022
DOI: 10.1038/s41598-022-22706-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative CT-assisted sacroiliac screws fixation for the treatment of posterior pelvic ring injury: a comparative study with conventional intraoperative imaging

Abstract: Pelvic injuries refer to the disruption of the inherent structural and mechanical integrity of the pelvic ring. Sacroiliac screw fixation technique is often applied for the treatment of posterior pelvic ring injury, which is prone to the iatrogenic injury. This study will compare the intraoperative and postoperative variables of patients underwent sacroiliac screw fixation with intraoperative CT and conventional imaging to evaluate the effect. Thirty-two patients with posterior pelvic ring injury treated by sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The radiation dosage for intraoperative CT is typically much higher than conventional fluoroscopy. 29 However, the previous paper demonstrated that total radiation exposure for intraoperative CT‐assisted posterior spinal fusion throughout treatment is not significantly different from fluoroscopy. 30 This may be related to the times of intraoperative fluoroscopy, duration of use, and the rate of pre‐and postoperative CT scans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The radiation dosage for intraoperative CT is typically much higher than conventional fluoroscopy. 29 However, the previous paper demonstrated that total radiation exposure for intraoperative CT‐assisted posterior spinal fusion throughout treatment is not significantly different from fluoroscopy. 30 This may be related to the times of intraoperative fluoroscopy, duration of use, and the rate of pre‐and postoperative CT scans.…”
Section: Discussionmentioning
confidence: 97%
“…Another issue that deserves more attention is radiation dosage. The radiation dosage for intraoperative CT is typically much higher than conventional fluoroscopy 29 . However, the previous paper demonstrated that total radiation exposure for intraoperative CT‐assisted posterior spinal fusion throughout treatment is not significantly different from fluoroscopy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances including CT guidance, navigation, multidimensional fluoroscopy, and biplanar fluoroscopy have all applied to this procedure. [22][23][24][25][26] However, the superiority of advanced imaging techniques over simple fluoroscopy with regard to the risks of neurovascular injury and implant malposition has not been clearly established. [22][23][24][25]27 The majority of pelvic fracture surgeons continue to use simple fluoroscopy, the most affordable and available imaging modality, for percutaneous pelvis fixation.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] However, the superiority of advanced imaging techniques over simple fluoroscopy with regard to the risks of neurovascular injury and implant malposition has not been clearly established. [22][23][24][25]27 The majority of pelvic fracture surgeons continue to use simple fluoroscopy, the most affordable and available imaging modality, for percutaneous pelvis fixation. 26,[28][29][30] Patient factors influence the quality and feasibility of fluoroscopic imaging in pelvis surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we took an individual approach to treatment, carefully assessing patients on preoperative X-ray and CT, and we referred to the following principles for the selection of the order of reduction: 1. In general, a displacement of the posterior pelvic ring of less than 1 cm is acceptable [ 23 , 24 ], whereas the displacement of the weight-bearing area at the top of the acetabulum should be less than 2 mm [ 25 27 ]. Therefore, we sought more anatomical reduction in the acetabulum during treatment.…”
Section: Discussionmentioning
confidence: 99%